The use of 3-methylene-2-pyrrolidone-based (co)polymers in industrial and biomedical applications - Heyns, Ingrid Marie (Stellenbosch : Stellenbosch University, 2018, 2018)
Thesis (PhD)--Stellenbosch University, 2018